Coupling of fully Eulerian and arbitrary Lagrangian-Eulerian methods for fluid-structure interaction computations - Wick, Thomas (Computational mechanics, 2013)
We present a specific application of the fluid-solid interface-tracking/interface-capturing technique (FSITICT) for solving fluid-structure interaction. Specifically, in the FSITICT, we choose as interface-tracking technique the arbitrary Lagrangian-Eulerian method and as interface-capturing technique the fully Eulerian approach, leading to the Eulerian-arbitrary Lagrangian-Eulerian (EALE) technique. Using this approach, the domain is partitioned into two sub-domains in which the different methods are used for the numerical solution. The discretization is based on a monolithic solver in which finite differences are used for temporal integration and a Galerkin finite element method for spatial discretization. The nonlinear problem is treated with Newton’s method. The method combines advantages of both sub-frameworks, which is demonstrated with the help of some benchmarks.
Gesehen am 04.09.2017